Ramucirumab for the treatment of advanced or metastatic non-small cell lung cancer. (1st December 2016) - Takeda, Koji; Daga, Haruko
ABSTRACT: Introduction : On 12 December 2014, the U.S. Food and Drug Administration (FDA) approved ramucirumab for use in combination with docetaxel for the treatment of patients with metastatic non-small cell lung cancer (NSCLC) with disease progression on or after platinum-based chemotherapy. Areas covered : This review discusses the best treatment strategy for ramucirumab, a vascular endothelial growth factor receptor-2 inhibitor for patients with advanced NSCLC. Expert opinion : The addition of ramucirumab to docetaxel in the treatment of patients with metastatic NSCLC who have progressed on or after platinum-based chemotherapy confers a 1.4-month improvement in overall survival, with an acceptable toxicity profile. The potential impact of the approval of the programmed death receptor-1 (PD-1)-blocking antibody nivolumab or pembrolizumab on the use of ramucirumab plus docetaxel in advanced NSCLC patient population is uncertain in clinical practice. In order to improve overall outcomes for patients with advanced NSCLC, both ramucirumab plus docetaxel and the PD-1-blocking antibody should be used in any treatment line.